Bureaucratic Cooptation in Program Evaluation: A Comparation Case in Indonesia and South Korea - Niken Paramarti Dasuki; Sukarso Sukarso (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2022)
Abstract The research about government program evaluation mostly uses an impact assessment, but this research would be using a meta-evaluation approach. The proposed research question is how the local government of Indonesia or the local bureaucracy evaluated their programs compared to South Korea. The method in this research is a comparative study between Indonesia dan South Korea, with data analysis from relevant documents. The result of the research proved that the evaluation patterns between programs seem similar. Both evaluation activities in South Korea and Indonesia tend to be dominated by their own bureaucracy; the difference is South Korea used to conceptualize activities while Indonesia does not. The evaluation activities only did the formalism part such as focusing on formal aspects than the aims of the program itself. Keywords: bureaucratic cooptation; evaluation; formalism; routine works Abstrak Berbeda dengan kebanyakan riset terkait evaluasi program pemerintah yang menggunakan penilaian dampak, penelitian ini menggunakan pendekatan meta-evaluation. Rumusan masalah yang diajukan adalah bagaimana pemerintah lokal di Indonesia atau birokrasi lokal melakukan evaluasi terhadap programnya. Metode yang akan digunakan untuk menjelaskan adalah pendekatan studi komparasi, dengan pengambilan data dari analisis dokumen-dokumen yang relevan dengan topik yang diambil. Hasil dari penelitian ini membuktikan bahwa pola evaluasi antar program cenderung mirip. Baik di Korea Selatan maupun Indonesia, aktivitas evaluasi cenderung didominasi oleh birokrasi; perbedaannya adalah di Korea Selatan lebih cenderung terkonseptualisasi namun di Indonesia cenderung tidak akurat. Aktivitas evaluasi hanya dilakukan sebagai formalitas dengan aspek-aspek formal dari program tersebut dibandingkan benar-benar melakukan evaluasi terhadap tujuan dari program terkait.